2017
DOI: 10.1038/ni.3849
|View full text |Cite|
|
Sign up to set email alerts
|

Human antibodies to the dengue virus E-dimer epitope have therapeutic activity against Zika virus infection

Abstract: The Zika virus (ZIKV) epidemic has resulted in congenital abnormalities in fetuses and neonates. Although some cross-reactive DENV antibodies can enhance ZIKV infection in mice, those recognizing the E-dimer epitope (EDE) can neutralize ZIKV infection in cell culture. We evaluated the therapeutic activity of human EDE monoclonal antibodies (mAbs) for their ability to control ZIKV infection in the brains, testes, placentas, and fetuses of mice. A single dose of EDE1-B10 antibody given three days after infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 53 publications
0
85
0
Order By: Relevance
“…In our experiments, sub-neutralizing doses of B10 did not result in enhanced ZIKV replication in mice (Supplementary Fig. S1), but nevertheless the possibility of antibody-dependent enhancement with a cross-reactive DENV/ZIKV-specific antibody requires further investigation, and if necessary Fc inactivating mutations could be incorporated 8 . Our data also raise the possibility of developing antibody therapeutics targeting both flaviviruses in endemic areas.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…In our experiments, sub-neutralizing doses of B10 did not result in enhanced ZIKV replication in mice (Supplementary Fig. S1), but nevertheless the possibility of antibody-dependent enhancement with a cross-reactive DENV/ZIKV-specific antibody requires further investigation, and if necessary Fc inactivating mutations could be incorporated 8 . Our data also raise the possibility of developing antibody therapeutics targeting both flaviviruses in endemic areas.…”
mentioning
confidence: 70%
“…Our laboratory and others have shown that ZIKV-specific neutralizing antibodies correlate with vaccine protection in both mice and monkeys 36 as well as with rapid control of viremia following infection in monkeys 7 . Several groups have also demonstrated therapeutic efficacy of ZIKV-specific mAbs in immunosuppressed mice 811 , and a cocktail of three ZIKV-specific mAbs that targeted domain III was shown to prevent ZIKV infection in nonhuman primates 12 . In the present study, we assessed the therapeutic and prophylactic efficacy of a potent ZIKV-specific antibody in rhesus monkeys.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccines for ZIKV are under development, but the path to approval may be exceedingly difficult because of antibody cross-reactivity with other flaviviruses and the possibility of disease enhancement (Bardina et al, 2017; George et al, 2017; Halstead, 2018; Harrison, 2016; Heinz and Stiasny, 2017; Katzelnick et al, 2017; Salje et al, 2018; Stettler et al, 2016). Passive administration of monoclonal antibodies represents an alternative approach to vaccines because human monoclonal antibodies can effectively neutralize the virus in vitro and protect against ZIKV infection in mice (Fernandez et al, 2017; Robbiani et al, 2017; Sapparapu et al, 2016; Stettler et al, 2016; Swanstrom et al, 2016; Yu et al, 2017). In addition, antibodies can be engineered to prevent interaction with Fcγ receptors that mediate enhancement and thus minimize the risk of disease enhancement (Beltramello et al, 2010).…”
Section: Introductionmentioning
confidence: 99%